2015
DOI: 10.1016/j.apjr.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Lauric acid abolishes interferon-gamma (IFN-γ)-induction of intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1) expression in human macrophages

Abstract: A B S T R A C TObjective: To investigate the effect of different concentrations of lauric acid on Intercellular Adhesion Molecule-1 (ICAM-1) and Vascular Cell Adhesion Molecule-1 (VCAM-1) expression in IFN-g stimulated human monocytic THP-1 cell line. Methods: THP-1 cell were cultured using Roswell Park Memorial Institute medium supplemented with 10% fetal bovine serum. THP-1 monocytes were firstly differentiated into macrophages by using phorbol-12-myristate-13-acetate. IFN-g response test was performed and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Resazurin metabolism of RAW macrophages was only marginally affected by fatty acid treatments, with a quadratic effect found with glycerol monolaurate. Past studies have found no effect of lauric acid on macrophage cell viability at lower concentrations (less than 20 μmol/L for 24 h incubation) [ 49 ], although another study with a 48 h incubation period found cytotoxic effects at greater concentrations (400 μmol/L) [ 50 ]. Judging from these studies, lauric acid likely impacts cell viability but only at greater concentrations with longer incubation times than those used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Resazurin metabolism of RAW macrophages was only marginally affected by fatty acid treatments, with a quadratic effect found with glycerol monolaurate. Past studies have found no effect of lauric acid on macrophage cell viability at lower concentrations (less than 20 μmol/L for 24 h incubation) [ 49 ], although another study with a 48 h incubation period found cytotoxic effects at greater concentrations (400 μmol/L) [ 50 ]. Judging from these studies, lauric acid likely impacts cell viability but only at greater concentrations with longer incubation times than those used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Wei-Siong et al [25] study, an ICAM expression was up-regulated by IFN through nuclear factor kappa B (NF interferon regulatory factor expression.…”
Section: Discussionmentioning
confidence: 98%
“…Lauric acid is a free saturated fatty acid in serum [24]. After a large amount of lauric acid is injected into the blood vessels, the blood vessels deposited in the corresponding blood vessels, which will cause vascular endothelial cells and vascular wall injury, induce thrombosis, cause local vascular circulation disorder, and eventually form the ischemic state of the local organism [25,26]. At present, lauric acid has been widely used to induce TAO model [21].…”
Section: Discussionmentioning
confidence: 99%